FRAUD RISK ASSESSMENT, AUDIT EXPERIENCE, AND AUDIT QUALITY: THE MODERATING ROLE OF PROFESSIONAL SKEPTICISM - Inggrit Larasati Br. Panggabean; Widia Astuty; Hastuti Olivia (ECOBISMA (JURNAL EKONOMI, BISNIS DAN MANAJEMEN), 2026)
PURPOSE - This paper aims to examine the effect of fraud risk assessment and audit experience on audit quality, with professional skepticism as a moderating variable, in Public Accounting Firms in Medan City. The study is based on the background of declining audit quality caused by weak fraud risk assessment, limited auditor experience, and low professional skepticism, which have led to audit failures and sanctions.METHODOLOGY - This study used a quantitative associative design with purposive sampling of 105 auditors from Public Accounting Firms in Medan City. Data were collected through Likert-scale questionnaires covering fraud risk assessment, audit experience, audit quality, and professional skepticism, which were tested for validity and reliability. The responses were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS.FINDING - The study found that fraud risk assessment and audit experience both positively affect audit quality. Professional skepticism further strengthens these effects, highlighting its crucial role in ensuring reliable and credible audits.